2014
DOI: 10.14257/astl.2014.47.87
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model of rolling force for electrical steel based on finite element method and neural network

Abstract: The rolling force prediction model for electrical steel in hot rolling was established. A 3D elastic-plastic finite element model of roll and strip was established by MSC. Marc software package. The influence of strip thickness, rolling temperature, strip width, friction coefficient, reduction and rolling speed on rolling force was attained by simulation. The rolling force prediction model for electrical steel in hot rolling was established based on FEA and BP neural network. The model with high accuracy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A predictive model of rolling force and tension profiles has been proposed by Kim et al 13 In their model, the pre-deformation has been taken into account, which has improved the prediction accuracy. A finite element model of hot strip rolling has been established by Cao et al 14 The numerical result shows that the rolling force increases as the strip width, rolling speed, rolling reduction, and friction coefficient increase. Lenard 15 carried out simulated work by FEM on cold strip rolling, and the result showed that the friction variation has apparent effect on the precision and convergence of simulations.…”
Section: Introductionmentioning
confidence: 99%
“…A predictive model of rolling force and tension profiles has been proposed by Kim et al 13 In their model, the pre-deformation has been taken into account, which has improved the prediction accuracy. A finite element model of hot strip rolling has been established by Cao et al 14 The numerical result shows that the rolling force increases as the strip width, rolling speed, rolling reduction, and friction coefficient increase. Lenard 15 carried out simulated work by FEM on cold strip rolling, and the result showed that the friction variation has apparent effect on the precision and convergence of simulations.…”
Section: Introductionmentioning
confidence: 99%